Status Hak Atas Tanah Penduduk Desa dalam Kawasan Hutan Perum Perhutani - Azzahra, Fatimiah (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2019)
This article aims to discuss the conflict of tenure rights between Perhutani and the community and the status of land held by the community after the entry into force of Presidential Regulation No. 86 of 2018 concerning Agraria Reform. The study uses a sociological juridical method. The location of the study is in the forest area of   Perhutani Public Corporation, Malang Regency. Data collection techniques using observation, interviews, and documentation. The results of the study show that conflicts over ownership of land rights between Perhutani and the community have been going on for a long time. Physically the land has been controlled by the community since the Dutch colonial era and passed down from generation to generation. The granting of permission to manage the land and payment of land tax strengthened the community’s argument about land ownership. The land status which is the object of the dispute is based on Presidential Regulation No. 86 of 2018 concerning Agrarian Reform became the authority of Perhutani Public Corporation. Communities can get ownership rights or get land compensation if the Ministry of Forestry releases the land.